Belgian Exceptionalism Belgian Politics between Realism and Surrealism - Caluwaerts, Didier; Reuchamps, Min (Routledge Advances in European Politics, 2022)
This book takes stock of Belgium's exceptional and - for some foreign observers -schizophrenic position in the political world and explains its idiosyncrasy to a non-Belgian audience. Offering a broad and comprehensive analysis of Belgian politics, the guiding questions throughout each of the chapters of this book are: Is Belgium a political enigma, and why? Along which axes is Belgium "exceptional" compared to other countries? And what insights does a comparative study of Belgian politics have to offer? The book therefore provides a critical assessment of how Belgian politics "stands out" internationally, both in good and bad ways - including consociationalism, federalism, democratic innovations, Euroscepticism, government formation, gender equality, among others - and which factors can explain Belgium's exceptional position. Based on cutting-edge research findings, the book will be of wide interest to scholars and students of Belgian politics, European Politics and Comparative politics.